DEMOKRASI DESA DALAM IMPLEMENTASI KEBIJAKAN USAHA EKONOMI DESA - Zalikha, Siti Nur (Fakultas Ilmu Sosial dan Ilmu Pemerintahan, 2018)
Badan Usaha Milik Gampong (BUMG) is a village economic institution established by the village government with capital ownership and management carried out by the government and the village community. The formation of BUMG Blang Krueng refers to the Aceh Besar Regent's Regulation Number 14 of 2008 concerning Village-Owned Enterprises (BUMG). The type of research used in this study is a type of qualitative research with a descriptive approach. The focus in this study is the application of village democratic principles to the BUMG as Village Economic Institutions. The results of this study found that adherence to democratic norms can go hand in hand with loyalty to the community and ultimately village democracy is no longer a universal device that is compelling or a mechanism and procedure that is independent of the experience of rural communities, but is related and tied to the lives of the people who run democracy. As reflected in a village economic institution in BUMG Blang Krueng, which succeeded in implementing village democracy in its establishment and management based on the principles of a) Village community interests, b) Deliberation, c) Participation, d) Volunteering, e) Tolerance, f) Humanity or humanist, g) Gender justice, and h) Transparent and accountable.